Novel cubosome based system for ocular delivery of acetazolamide - Hoda E. Teba; Islam A. Khalil; Heba M. El Sorogy (Taylor & Francis Group, 2021)
Acetazolamide is the drug of choice for glaucoma treatment in an emergency. However, it is not available in any topical formulation and it is available only as systemic tablets. Despite its efficiency as a drug in decreasing intraocular pressure, it has negative systemic effects as renal toxicity and metabolic acidosis. Moreover, it suffers from poor aqueous solubility and low corneal permeability limiting its ocular bioavailability and its use topically. Cubosomes have enormous advantages as a drug delivery system, most importantly, high surface area, thermal stability, and ability to encapsulate hydrophobic, amhiphilic, and hydrophilic molecules. Herein, we have exploited the unique properties of cubosomes as a novel nano-delivery system for acetazolamide as eye drops dosage form for glaucoma treatment. Different acetazolamide-loaded cubosomes have been developed and evaluated. The best-optimized formulation (F5), was cubic shaped structure, with an average particle size of 359.5 ± 2.8 nm, surface charge −10.8 ± 3.2 mV, and 59.8% entrapment efficiency. Ex-vivo corneal permeation studies have revealed a 4-fold increase in acetazolamide permeability coefficient compared to that stated in the literature. F5 showed superior therapeutic efficacy represented by a 38.22% maximum decrease in intraocular pressure vs. 31.14 and 21.99% decrease for the commercial Azopt® eye drops and Cidamex® tablets, respectively. It also exhibited higher (AUC0-10) compared to Azopt® eye drops and Cidamex® tablets by 2.3 and 3 times, respectively. F5 showed mean residence time 4.22 h vs. 2.36 and 2.62 h for Azopt® and Cidamex® with no eye irritation observed according to the modified Draize test. To the best of our knowledge, this is the first study for developing acetazolamide-loaded cubosomes as the topical delivery system for glaucoma treatment.